Theoretical study of structural, electronic, optical and thermoelectric properties of XN (X = Sc, Y). (15th November 2021) - Azouaoui, A.; Benzakour, N.; Hourmatallah, A.; Bouslykhane, K.
Abstract: The structural, electronic, optical, and thermoelectric (TE) properties of XN (X=Sc, Y) were computed using density functional theory (DFT) based on the generalized gradient approximation and semi-classical Boltzmann transport theory. The present XN are found stable in rocksalt (RS) structure with nonmagnetic configuration and have shown semiconductor behavior with small indirect band gaps. Based on the analysis of the elastic constants and their derived parameters, these compounds are predicted the brittle nature and have an ionic bond and are found mechanically and thermodynamically stable. The TE properties such as Seebeck coefficient, electrical conductivity, electronic thermal conductivity, power factor and figure of merit are calculated. It is found that these properties increased with an increase in temperature for ScN and decreased for YN. At the temperature of 300K, the XN exhibits a high Seebeck coefficient, electrical conductivity and power factor. The calculated values of the figure of merit are 0.28 and 0.83 for ScN and YN at 300K, respectively. The imaginary and real parts of dielectric complex function, refractive index and absorption coefficient are calculated. The reflectivity is found less than 40% and the refractivity index about 2–3 in the visible light region. These properties make YN promising material for thermoelectric and optoelectronic applications.